The Huguenots: their settlements, churches, and industries in England and Ireland - Smiles, Samuel (Cambridge library collection. British & Irish history, 17th & 18th centuries, 2015)
One of the most popular Victorian writers, Samuel Smiles (1812–1904) made his name in 1859 with the original self-improvement manual, Self-Help. His highly successful multi-volume Lives of the Engineers contained biographies of men who had, like him, achieved greatness not through privilege but through hard work. In this 1867 book, Smiles examines the part played in British society and economic life by the Protestants who either left France to escape religious persecution or were expelled after the revocation of the Edict of Nantes in 1685. The appeal of the topic to Smiles probably lay in the proverbial industry and hard work of these refugees, who arrived penniless but rapidly made their way to prosperity, to social acceptance, and, in only two or three generations, to some of the highest positions in the land. This fascinating work covers the history of the Huguenots and discusses some of their famous descendants.